Análise da geração distribuída sob a perspectiva de maximização de potência injetada em sistemas de distribuição - Tonhá, Henrique Mesquita (2017)
Electricity distribution networks around the world are able to receive generators installed along their length. As the studies of the impacts of distributed generators emerge and deepen in the solution of the problems arising from the granting of installation of DGs, their benefits become more attractive than impediments not yet overcome and their dissemination becomes a irreversible tendency. One of the inconveniences faced by enterprising to the electrical system is the power limitation to be injected in the network to the situation that the enterprising one behaves like exporter, this limitation can become a factor of discouraging his input in the system. In this sense, this work searches through a well-known tool of load flow - OpenDSS to carry out tests proposing the substitution of the conductor in part of the network in order to enable more ambitious distributed generation projects from the point of view of the injected power. In addition, the impact of the voltage regulator, often found in the networks, on the maximum permissible potency to be inserted in the studied network, as well as the impact on the electric losses profile and the proposed overcurrent protection are also analyzed. The tests demonstrated that the substitution of the conductor was adequate for the maximization of power, especially when the network operates with voltage regulator. In view of the distributed generation connection and the replace the cable proposed of part of the network, the losses presented a relative reduction and the protection times were reduced due to the necessary replacement of some devices